Flagella and motility behaviour of square bacteria. - Alam, M (1984)
Square bacteria are shown to have right-handed helical (RH) flagella. They swim forward by clockwise (CW), and backwards by counterclockwise (CCW) rotation of their flagella. They are propelled by several or single filaments arising at several or single points on the cell surface. When there are several filaments a stable bundle is formed that does not fly apart during the change from clockwise to counterclockwise rotation or vice versa. In addition to the flagella attached to the cells, large amounts of detached flagella aggregated into thick super-flagella, can be observed at all phases of growth.